Verified Interoperable Implementations of Security Protocols - Bhargavan, Karthik; Fournet, Cédric; Gordon, Andy; Tse, Stephen (IEEE, 2007)
We present an architecture and tools for verifying implementations of security protocols. Our implementations can run with both concrete and symbolic cryptographic libraries. The concrete implementation is for production and interoperability testing. The symbolic implementation is for debugging and formal verification. We develop our approach for protocols written in F#, a dialect of ML, and verify them by compilation to ProVerif, a resolution-based theorem prover for cryptographic protocols. We establish the correctness of this compilation scheme, and we illustrate our approach with protocols for Web Services security.
Computer Security Foundations Workshop, 2006. 19th IEEE